Pemikiran Richard C. Martin Tentang Islam dan Studi Agama Serta Implikasinya dalam Kajian Psikologi - Tri Na'imah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
Religion as a belief and way of life is a very important thing in human life. Religion is understood to be able to provide confidence, motivation and relevance wherever and whenever (fi kulli zaman wa makan). Therefore religion must be understood scientifically, objectively and openly in the midst of complexities and diverse perspectives. Religion must be placed in the realm of scientific objects that are ready to be studied, examined and developed in all dimensions and perspectives of Muslims (Oksidentalist) and non-Muslims (orientalist). To answer anxiety and solution, Richard C. Martin offers three approaches, namely the approach of data fields, phenomenology and psychology. This research is a literature study. The source of the data is obtained from primary data in the form book titled â€œApproaches to Islam in Religious Studies" with editor Richard C. Martin and secondary in the form of research related to research. This analysis uses content analysis. The results of this study are that disclosure of issues of religious studies through data fields, namely data about Islam which consists of historical and geographical data. While the types of data consist of textual types, socio-historical data, and ritual-symbolic data. The solution to Martin's approach to Islamic studies is his solution idea in the form of a phenomenological approach to solve insider and outsider problems. The phenomenological approach can be used as a basis for combining Islamic studies and psychological studies to examine the problem of one's religious behavior. Agama sebagai keyakinan dan pedoman hidup (way of live) merupakan hal yang sangat penting dalam kehidupan manusia. Agama dipahami mampu akan memberikan keyakinan, motivasi dan relevan dimanapun dan kapanpun (fi kulli zaman wa makan). Oleh karena itu agama harus dipahami secara ilmiah, objektif dan terbuka di tengah-tengah kompleksitas dan cara pandang yang beragam. Agama harus di tempatkan pada ranah objek ilmiah yang siap diteliti, dikaji dan dikembangkan dalam segala dimensi dan perspektif muslim(Oksidentalis) maupun non muslim (orientalis). Untuk menjawab kegelisahan dan solusi maka, Richard C. Martin menawarkan tiga pendekatan yakni pendekatan data fields, fenomenologi dan psikologi. Penelitian Ini merupakan studi pustaka. Sumber data diperoleh dari data primer berupa buku berjudul â€œApproaches to Islam in Religious Studiesâ€ dengan editor Richard C. Martin dan sekunder berupa putaka yang berkaitan dengan penelitian. Analisis ini menggunakan content analysis. Hasil penelitian ini menunjukkan bahwa pengungkapan terhadap isu-isu studi agama melalui data field yaitu data tentang Islam yang terdiri dari data historis maupun geografis. Sedang jenisjenis data terdiri dari jenis-jenis tekstual, data sosial-historis, serta data ritualsimbolis. Solusi pendekatan Martin untuk studi Islam adalah gagasan solutifnya berupa pendekatan fenomenologi untuk memecahkan problem-problem insider dan outsider. Pendekatan fenomenologi dapat dijadikan sebagai dasar memadukan studi Islam dan kajian psikologis untuk mengkaji masalah perilaku keagamaan seseorang.